Assessing the Efficiency and Effectiveness of MRP System in Manufacturing Industries of North India - Singh, Ramanpreet (My University, 2014)
In today's dynamic industrial environment, Inventory control is an important parameter in production systems. To guard against inventory shortages or surprises of stock, proper policy for inventory control should be utilized, which can overcome inventory shortage losses and lessens the capital assets. MRP techniques are widely used to control inventories and to avoid stock out while retaining a high level of service. There are a number of factors which influence the parameters of the MRP system. This study has concentrated to examine the implementation aspects (organizational and technological factors) of MRP system and their effect on the parameters of MRP system to assess the efficiency and effectiveness of MRP system in the northern industrial belt of India. On the basis of implementation aspects, six hypotheses have been assumed to validate the goal of this study. The design of the questionnaire was based on the success measure variables and determinant variables which affect the efficiency and effectiveness of MRP system. The success measurements and determinant variables have been adopted from the previous studies of Sum et al. (1993) and Cheng (1997). Thirty numbers of survey responses were analyzed and presented by using SPSS software. Survey summary showed the profiles of MRP user, average rating of system parameters, and the degree of computerization, benefits and implementation problems of the MRP system. Various responses of the survey concluded that the different organizational (top management support, user training level) and technological factors (software customization, degree of computerization, suitability of software) have a significant effect on the parameters (performance and accuracy) of MRP system on which the system efficiency and effectiveness depend. The other results of this study, help manufacturing companies to implement an MRP system to strategize their efforts and process to ensure successful implementation
ME, MED
Keywords: MRP System; Effectiveness